Indicadores de insensibilização em tilápia-do-Nilo - Carlos, Clarissa Lerois [UNESP] (2015)
The reduction of suffering at the time of production of animal slaughter is current concern, given the high production of Nile tilapia (Oreochromis nilocticus), monitoring the degree of pre-slaughter in fish stunning needs more study when compared to other species. And slaughter the most critical stage of breeding, the application of good management practices that meet the animal welfare becomes essential for success at this stage. Given the importance of exploring methods to unveil the fish level of consciousness at the time of stunning, this study aimed to test whether the bristling reflection of the dorsal fin (REN) produced by manual stimulation may be a candidate for sensitivity loss indicator . To this end, we explore, initially, the effects of benzocaine on reflection, anesthetic widely used for fish. Latency, duration and REN recovery rate was observed. We then apply stunning methods commonly used in fish farming, they are: termonarcose narcosis and carbon dioxide, in order to test whether the REN disappears as observed with benzocaine. In addition, we tested the reflection of eye rotation (RO) for the purpose of comparison between the REN and RO methods and the ability to correct posture during induction. All fish lost reflections analyzed at one point of the experiments, so our results show that the REN insensitivity can be indicator in the Nile tilapia. However, although the RO have more rapid loss and slower recovery than REN, there was little difference in time. So for RO and REN are reflexes are important to indicate stunning, and then it is possible to combine the two methods as a strategy for assessing unconsciousness in Nile tilapia